Enhanced Graph Theoretic Modeling for Estimating Node Localization and Reachability in WSN - Dr. A. Sangeetha Devi, Mrs. A. Kalaivani (International Journal of Advanced Science and Technology, 2020)
A graph based approximation is developed for calculating the localization, reachability and sensing the node connectivity with randomly positioned nodes in Wireless Sensor Networks (WSNs). This approximation is achieved by taking into account the graph property in which edge appears between any vertices that denote sensors in the neighboring communication area. The key analysis is to create the communication area request enclosed by the minimum one node with the predicted amount of nodes in the specified network. The probability of connectivity of specified node is completely calculated and approximated here. The approximation results in the collaboration of connected node density for transmitting data. The relationship amongst the nodes and the region of coverage by the sensors is also investigated. This helps in designing any application related to sensor network effectively and to calculate the energy for transmission.